Multimedia Design for Geometric Optical Material Using Professional Adobe Flash CS5 Software - Rafiah, Dian; Rahim, Revalia (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2016)
This research is motivated by the importance of the basic physics II course as the basis for physics education programs. The use of modern tools that are in line with the demands of technological developments such as computers is one of the learning media that is popular with most students. This research aims to design learning media for Basic Physics II courses using professional Adobe Flash CS5 software on Geometric Optics material, as well as knowing students' perceptions of the media that has been developed. This research is development research (Research and Development). From the results of questionnaire trials on physics education students at Jambi University, semester 5, class of 2013, it was found that the instrument had high reliability and could be trusted for collecting research data. Meanwhile, data collection on students' perceptions of the media was carried out on physics education students at Jambi University, semester 3, class of 2014. After data collection and analysis, the average percentage was 82.47% (good). Based on the results obtained in the research, it can be concluded that the learning media design for the Basic Physics II course using Adobe Flash professional C56 software on Geometric Optics material is good/suitable for use.